1980
DOI: 10.1007/bf02414732
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of estuarine animals to cadmium pollution

Abstract: Toxic effects of cadmium contamination may be observed at all levels of organismic organization. In estuarine areas the sensitivity of euryhaline species to acute Cd toxicity is strongly modified by various abiotic factors, whereas long-term threshold values are less dependent on environmental parameters. Experiments with larval stages of the mollusc Mytilus edulis reveal that Cd effects on life functions such as development and growth are differentially modified by temperature and salinity. High Cd concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…Theede et al (1979) and Jones (1975) found less tolerance to cadmium at low salinities and high temperatures and concluded that species living near their distributional limits are sensitive to lower pollution levels than those living at optimum environmental conditions. Theede (1980) later observed that sensitivity to chronic exposure to cadmium is less dependent on environmental salinity and temperature than are the results of acute tests which use high cadmium concentrations.…”
Section: Bahiamentioning
confidence: 99%
“…Theede et al (1979) and Jones (1975) found less tolerance to cadmium at low salinities and high temperatures and concluded that species living near their distributional limits are sensitive to lower pollution levels than those living at optimum environmental conditions. Theede (1980) later observed that sensitivity to chronic exposure to cadmium is less dependent on environmental salinity and temperature than are the results of acute tests which use high cadmium concentrations.…”
Section: Bahiamentioning
confidence: 99%
“…Since benthic fauna both influence and are influenced by conta- tight coupling between the geochemical fate and biological effects of sediment-associated contaminants (Rhoads 1974, Reynoldson 1987. Like many anthropogenically derived metals, cadmium accumulates in aquatic sediments and reaches its highest concentrations mainly in coastal and estuarine areas (Theede 1980, Ankley et al 1994, Campbell & Tessier 1996. Benthic organisms are able to accumulate cadmium via overlying water, porewater and ingested particles, and the determination of the relative importance of these different routes of uptake and subsequent toxicity to bottom-dwelling organisms is critical for assessing the risks associated with contaminated sediments.…”
Section: Introductionmentioning
confidence: 99%
“…I was chosen for the present study, because its feeding strategy includes processing large quantities of fine-grained sediment and because the environments containing organically enriched sediments, which are ideal habitats for thls species, often are sites of high heavy metal contamination (Pearson & Rosenberg 1978). Cadmium was chosen because it is characterized as one of the most toxic heavy metals (Theede 1980, Baudo & Muntau 1990) and is known to have an important influence on the energetics of benthic invertebrates (e.g. Theede 1980, Forbes 1991, Forbes & Depledge 1992.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data on the effects of variations in salinity and temperature, which are comparable to those encountered in estuaries, in relation to chromium toxicity are not available for animals. Where such studies have been conducted with other metals (Theede, 1980;Coglianese, 1982;Cotter et al, 1982;Denton and Burdon-Jones, 1982), they have generally shown that the acute toxicity of heavy metals increases as temperature increases and as salinity decreases. Frey et al (1983) have reported that hexavalent chromium is very inhibitory to the growth of estuarine phytoplankton in fresh-water, but less inhibitory as salinity increases.…”
Section: Introductionmentioning
confidence: 99%